2021
DOI: 10.24953/turkjped.2021.03.010
|View full text |Cite
|
Sign up to set email alerts
|

The comparison and diagnostic accuracy of different types of thermometers

Abstract: Background. Fever is one of the leading causes of hospital admissions in children. Although there are many ways to measure body temperature, the optimal method and the anatomic site are still controversial. In this study, we aimed to evaluate the performance of new methods of measuring body temperature and to compare the accuracy, sensitivity and specificity of these methods.Methods. The body temperatures of the patients who were hospitalized as inpatients or who presented to the emergency room as outpatients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Research is exploring alternative routes[ 5 - 11 ]. Tympanic thermometry has been recognized by different studies for its accuracy and convenience compared with the rectal and axillary routes[ 10 , 11 ]. It measures the thermal radiation of the tympanic membrane using infrared radiation emission detectors, either through thermopile or pyroelectric sensors[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research is exploring alternative routes[ 5 - 11 ]. Tympanic thermometry has been recognized by different studies for its accuracy and convenience compared with the rectal and axillary routes[ 10 , 11 ]. It measures the thermal radiation of the tympanic membrane using infrared radiation emission detectors, either through thermopile or pyroelectric sensors[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/s23177439/s1, Table S1: NCIT; Table S2: IRT. References [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86] are cited in the Supplementary Materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The results from the obtained data in the above figures showed that Thermal cameras were used at low level in developing countries while in developed countries are commonly used. In pandemic situations like COVID-19, the thermal camera acted as an element of security (Erdem et al, 2021). It took body temperature in real time without contact.…”
Section: Demographics Characteristicsmentioning
confidence: 99%